The Influence of Competition, Project Characteristics, and Provider Capacity on Tender Bidding for Construction Works in Jember Regency Government - Karina Aprilia Permatasari; Wahyuni, Nining Ika; Irmadariyani, Ririn (West Science Accounting and Finance, 2025)
This study aims to analyze the influence of competition, project characteristics, and provider capacity on the decision of construction service providers in bidding for tenders in Jember Regency. The approach used was quantitative with an explanatory study. The data analysis technique used was Structural Equation Modelling–Partial Least Squares (SEM-PLS) through the SmartPLS 4.0 application. Data were collected through a questionnaire from 100 respondents determined using the Lemeshow formula. The results of the study showed that the three independent variables significantly influence the tender bidding variable. Competition has a positive influence, indicating that healthy competition encourages providers' participation. Project characteristics also have a positive influence, where informative and realistic project specifications increase the providers' interests. Provider capacity indicates that internal readiness, such as experiences, resources, and financial capability, is the main determinant of participation in a tender. Implication of this finding highlights the need for preparing a transparent tender document and increasing provider capacity to support the effectiveness of the procurement process. This study contributes to the development of an evaluation model for provider participation in public sector construction procurement and as a reference for more competitive and integrated procurement policies.